Mitochondrial autophagy in the sleeping brain - Mauri, Sofia; Favaro, Mariavittoria; Bernardo, Greta; Mazzotta, Gabriella M.; Ziviani, Elena (Frontiers in Cell and Developmental Biology, 2022)
A significant percentage of the mitochondrial mass is replaced on a daily basis via mechanisms of mitochondrial quality control. Through mitophagy (a selective type of autophagy that promotes mitochondrial proteostasis) cells keep a healthy pool of mitochondria, and prevent oxidative stress and inflammation. Furthermore, mitophagy helps adapting to the metabolic demand of the cells, which changes on a daily basis. Core components of the mitophagy process are PINK1 and Parkin, which mutations are linked to Parkinson’s Disease. The crucial role of PINK1/Parkin pathway during stress-induced mitophagy has been extensively studied in vitro in different cell types. However, mitophagy seems to be only slightly affected in PINK1 KO mice and flies, putting into question the physiological relevance of this pathway in vivo. In this Mini Review we want to summarize the recent advances in the field, and add another level of complexity by focusing attention on a potentially important aspect of mitophagy regulation: the implication of the circadian clock. The circadian clock controls many aspects of mitochondrial physiology, including mitochondrial morphology and dynamic, respiratory activity, and ATP synthesis. Furthermore, one of the essential functions of sleep, which is controlled by the clock, is the clearance of toxic metabolic compounds from the brain, including ROS, via mechanisms of proteostasis. Very little is known about a potential role of the clock in the quality control mechanisms that maintain the mitochondrial repertoire healthy during sleep/wake cycles. More importantly, it remains completely unexplored whether (dys)function of mitochondrial proteostasis feedbacks to the circadian clockwork.